Prevalence and reasons for smoking among upper secondary schoolboys in Hulu Langat, Malaysia - Khairani O; Norazua R; Zaiton A (Penerbit UKM, 2007)
Smoking in adolescence is a great health concern as it is related to many chronic diseases and mortality in later life. It is also associated with other high-risk behaviours among adolescents. The objective of this study was to determine the prevalence and reasons for smoking among upper secondary schoolboys. This was a cross-sectional study conducted among Form 4 and Form 5 students. Three schools in the District of Hulu Langat were identified and students from these schools were selected randomly. The students were given a self-administered questionnaire. A total of 343 students were included in the study. The prevalence of smoking among the schoolboys was 37%. Although the majority of them initiated smoking between 13-15 years old (67%), 21% of them began smoking below 12years of age (primary school). There was a significant association between adolescent smoking and smoking among family members (p<0.05). The common reasons reported for initiating smoking were curiosity (69%) and peer pressure (51%). However, the common reasons for continuing smoking were stress (70%) and addiction (49%). Schoolwork was reported as the most important factor which contributed to their stress. Smoking prevention programmes should begin early in primary schools. Adolescents should be educated on effective coping strategies in managing stress and learning to be assertive